Effectiveness Of Phbs Android Educational Games On Clean And Healthy Living Behaviors In Primary School Children In The Coastal Area Of Bengkulu City - Marsofely, Reka Lagora; Marleni, Wisuda Andeka; Widiyati, Sri; Surahmi, Fajar (Jurnal Riset Kesehatan, 2024)
School-aged children are a strategic or appropriate target for implementing health programs because apart from being large in number, they are also a target that is easy to reach and can be well organized. The high level of student ignorance regarding clean and healthy living behavior (PHBS) is still due to environmental factors, influence from peers, and educational patterns provided by parents. One way to increase children's knowledge is by providing education using a method that children like, namely through games. This research aims to determine the effectiveness of educational games on knowledge and attitudes about PHBS among elementary school children in the coastal area of Bengkulu City. This type of research used a quantitative method with quasi experimental design two group pretest posttest. The sample was taken from 70 people using a simple random sampling technique. Data were analyzed using the paired T-Test. The results of statistical tests show that there is an increase in average knowledge after providing educational game intervention (p=0.000, t= -5.111, one tail) and there was an increase in average attitude after providing the educational game intervention (p=0.000, t=-1.548, one tail). The intervention was effective in knowledge and attitudes about PHBS among elementary school children in the coastal area of Bengkulu city. It is hoped that this research can be used as a medium to increase knowledge and attitudes towards implementing PHBS in children.